Peran Kader Pkk Terhadap Pola Asuh Orang Tua Di Desa Singaraja Kecamatan Indramayu - Fauziah, Hilda Nur; ., Ilyas (Peneliti.net, 2023)
This study aims to describe the role of PKK cadres in parenting parents in Singaraja Village. This study used a qualitative approach, with 5 research subjects consisting of 1 Secretary of Singaraja Village, 1 Chairperson of the Singaraja Village PKK, 1 Chairperson of the Singaraja Village PKK Working Group and 2 Singaraja Village Communities. Data collection techniques used in the form of observation, interviews and documentation. The validity of the data using technique triangulation and source triangulation. Data analysis techniques use the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the role of PKK cadres for the people of Singaraja Village is important and a necessity for the community. The program run by PKK cadres certainly fits the needs and has many benefits for the community. PKK Cadres of Singaraja Village play an active and participatory role in implementing programs aimed at family welfare. The supporting factors of the PKK program are encouragement from the government, while the inhibiting factors are the lack of public awareness, community participation in all forms of activities, and many people who still do not understand the importance of parenting in the family.